The meanings of the noun love in some English expressions (from cognitive semantics perspective) = Tìm hiểu ý nghĩa của danh từ Love" trong một số cụm từ trong tiếng Anh xét từ góc độ ngữ nghĩa học tri nhận. M.A Thesis Linguistics: 60 22 15" - Nguyễn, Thị Thơm (University of Languages and International Studies, 2017)
43 p. + CD-ROM